2019
DOI: 10.1097/pas.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Molecular and Immunohistochemical Analyses of Endometrial Clear Cell Carcinoma Show that POLE Mutations and DNA Mismatch Repair Protein Deficiencies Are Uncommon

Abstract: Endometrial clear cell carcinoma (ECCC) is an uncommon histotype without unique identified molecular alterations. Recently, The Cancer Genome Atlas molecular subtypes have been reported in ECCC. ECCC cases were collected from 11 institutions with diagnoses confirmed by morphologic review and immunohistochemistry. DNA mismatch repair (MMR) proteins, p53 expression, and ARID1A expression was assessed by immunohistochemistry on tissue microarrays. Targeted next-generation sequencing was completed for POLE, TP53, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
0
25
1
Order By: Relevance
“…Yet an important question is why are pathologists reluctant to use these tests for histotyping? For example, DeLair et al reported in another recent issue of this Journal that 6/32 (19%) pure endometrial clear cell carcinomas were mismatch repair‐deficient , which according to Drs McAlpine, Leon‐Castillo, and Bosse demonstrates “… ‘proof of concept’ that molecular classification may be clinically meaningful across all histotypes.” In contrast to this, we found no mismatch repair deficiency in a total of 51 pure endometrial clear cell carcinomas from two independent series that underwent immunohistochemical confirmation (Napsin A/HNF1β/ER) . Instead, we found a frequency of mismatch repair deficiency of 65% (27/41 cases) reported as ‘mixed endometrioid clear cell carcinoma’ .…”
Section: Implementation or Integration Of Molecular Subclasses?contrasting
confidence: 92%
“…Yet an important question is why are pathologists reluctant to use these tests for histotyping? For example, DeLair et al reported in another recent issue of this Journal that 6/32 (19%) pure endometrial clear cell carcinomas were mismatch repair‐deficient , which according to Drs McAlpine, Leon‐Castillo, and Bosse demonstrates “… ‘proof of concept’ that molecular classification may be clinically meaningful across all histotypes.” In contrast to this, we found no mismatch repair deficiency in a total of 51 pure endometrial clear cell carcinomas from two independent series that underwent immunohistochemical confirmation (Napsin A/HNF1β/ER) . Instead, we found a frequency of mismatch repair deficiency of 65% (27/41 cases) reported as ‘mixed endometrioid clear cell carcinoma’ .…”
Section: Implementation or Integration Of Molecular Subclasses?contrasting
confidence: 92%
“…The immunostaining results of the different markers were read and scored as described previously 21–25. For all of the markers, except PTEN and IMP3, a nuclear stain was expected to demonstrate their expressions.…”
Section: Methodsmentioning
confidence: 99%
“…Study methods are reported in detail in the Data . Five studies with a total of 162 patients with CCC were included. The characteristics of the included studies are shown in Table .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%